Long-Term Efficacy of a Mini-Course in Radiation-Reducing Techniques in Invasive Cardiology - Kuon, E.; Empen, K.; Weitmann, K.; Staudt, A.; Hummel, A.; Dörr, M.; Reffelmann, T.; Hoffmann, W.; Felix, S. B. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Purpose: To validate the long-term efficacy of a 90-min. educational mini-course in less-irradiating cardiac interventional techniques.Materials and Methods: Before, two months after, and two years after the mini-course (periods I, II, and III), we analyzed the following radiation dose parameters for ten coronary angiographies (CA), performed by each of 7 cardiologists: total dose-area product (DAP), radiographic and fluoroscopic DAP fractions, number of radiographic frames and runs, and fluoroscopy time.Results: The median patient DAP for periods I, II and III was 31.4, 15.8 and 8.5 Gy × cm2, respectively. The long-term effect was related to shorter median fluoroscopy times (180, 172, and 120 s), shorter (57, 52, and 45) and fewer (12, 12, and 10) radiographic runs, consistent collimation and restriction to an adequate image quality. Both radiographic DAP/frame (28.7, 17.0, and 18.4 mGy × cm2) and fluoroscopic DAP/second (45.7, 24.2, and 10.0 mGy × cm2) decreased significantly. The multivariate linear regression analysis confirmed the increasing efficacy of the mini-course itself (–44.6 and –60.7 %), and revealed a decreasing influence of the interventionalist’s experience (–8.6 % and –4.9 % per 1,000 CAs, lifelong performed until the mini-course). The number of CAs performed after the mini-course did not influence the long-term DAP results.Conclusion: The presented educational mini-course allows a significant, long-lasting, and apparently ongoing reduction of patient radiation exposure due to CA. A self-surveillant documentation of relevant radiation parameters is well suited to monitor and improve each operator’s individual long-term radiation-reducing efforts.
Keywords: radiation safety; coronary angiography; radiography; fluoroscopy; education; QA/QC